Profile of Students' Critical Thinking in Mathematical Contextual Problem Solving in terms of Independent Learning - Wardah, Afifah; Sumartono, Sumartono; Prastiwi, Lusiana (International Journal of Social Science, Education, Communication and Economics, 2022)
Critical thinking is a careful and calculating thinking activity using complex reasoning and is essential in solving mathematical contextual problems. This study aimed to describe the profile of students' critical thinking in solving mathematical contextual problems in terms of student independence. This study uses a qualitative descriptive method with the subject of students at SMK, Dr. Soetomo Surabaya. Data collection techniques using questionnaires, interviews, and documentation. The collected data is then analyzed through four stages: data reduction, triangulation, data presentation, and conclusion. The results showed that the critical thinking profile of subjects with high levels of learning independence was more complete than subjects with moderate and low levels of learning. Subjects with a high level of learning independence have a critical thinking profile that can use the right strategy to solve problems, complete, and correctly do calculations and explanations.